1980
DOI: 10.1111/j.1432-1033.1980.tb04821.x
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of the Ligand-Binding Sites in the Acetylcholine-Receptor Oligomer from Muscle and from Electric Organ. Measurement by Affinity Alkylation with Bromoacetylcholine

Abstract: 1. The affinity alkylation reaction of the cholinergic, depolarising ligand, bromoacetylcholine with reduced acetylcholine receptor in the membrane fragments of Torpedo marmorata and in Triton-solubilised receptor from cat denervated muscle has been studied.2. Brief pretreatment with 100 pM bromoacetylcholine abolishes all [3H]a-neurotoxin binding in both cases.3. In the receptor from each of these sources, the number of sites of specific a-neurotoxin binding is exactly equal to the number of sites that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
3
2

Year Published

1982
1982
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 28 publications
9
64
3
2
Order By: Relevance
“…At different times, the free sulfhydryls were reacted with an excess of bromoacetylcholine (BAC, 10 mM) and the residual c~-toxin binding sites were quantified. These experiments showed that the time-course that is required to completely reduce the disulfide bond adjacent to the ligand binding site was about 5 min in the case of ARA (20/.tM), 20 min for DTT (200/zM), in agreement with previous reports [4], and up to 2 h for MeRA or DTT at 20/tM (Fig. 3).…”
Section: Kinetic Of the Disulfide Bond Reduction By Ara Dtt Orsupporting
confidence: 79%
See 1 more Smart Citation
“…At different times, the free sulfhydryls were reacted with an excess of bromoacetylcholine (BAC, 10 mM) and the residual c~-toxin binding sites were quantified. These experiments showed that the time-course that is required to completely reduce the disulfide bond adjacent to the ligand binding site was about 5 min in the case of ARA (20/.tM), 20 min for DTT (200/zM), in agreement with previous reports [4], and up to 2 h for MeRA or DTT at 20/tM (Fig. 3).…”
Section: Kinetic Of the Disulfide Bond Reduction By Ara Dtt Orsupporting
confidence: 79%
“…A well-documented model for testing this concept is the disulfide bond located between Cys-192 and Cys-193 of the a-subunit of the nicotinic acetylcholine receptor (AChoR) [1,2]. These residues are involved in the binding site of acetylcholine and have already been labeled, after reduction with DTT, with an agonist (BAC) [3][4][5][6][7] or an antagonist (MBTA) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Conservation of this disulfide bond suggests that it has an important structural or functional role in this family of proteins with a shared evolutionary history. We found no evidence that BAC labels the neuronal AChR in a biphasic manner, as is known for electric organ and skeletal muscle AChR due to preferential labeling of 1 of the 2 binding sites (Wolosin et al, 1980). Similarly, the inhibition of 3H-nicotine binding to neuronal AChR by curare (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…This feature is conserved in electric organ and skeletal muscle AChRs (Damle et al, 1978;Wolosin et al, 1980), in the brain aBGT binding protein (Kemp et al, 1985;Norman et al, 1982), as well as in neuronal AChRs. Conservation of this disulfide bond suggests that it has an important structural or functional role in this family of proteins with a shared evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation